Effect of Acupoint Embedding on Serum Leptin and Hypothalamus Leptin Receptor Expression in Rats with Simple Obesity. (6th October 2021) - Yang, Qiming; Xing, Liwei; Dong, Qinzuo; Chen, Hongxi; Xia, Chunlin; Yue, Xianwu; Wang, Yuanfeng; Li, Li; Luo, Yingjing; Lai, Mingxing; Zhao, Dong; Zhang, Zhiyan; et al.
Abstract : Background . Acupoint embedding treatment on obesity has been applied in clinical practice for many years and has achieved obvious efficacy. However, animal experimental studies on acupoint embedding are relatively few, and its mechanism remains unclear. Methods . We established a simple obese rat model using a high-fat diet for 8 weeks. Acupoint embedding therapy was performed once a week for 4 weeks. After the treatment, serum leptin, triglyceride (TG), cholesterol (TC), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) levels were detected by radioimmunoassay, HE staining was used for fat morphology analysis, and immunohistochemical method was used to detect the expression of leptin receptor in hypothalamus. Results . Compared with model group, acupoint embedding treatment can reduce body weight and Lee's index, reduce serum leptin, TG, TC, and LDL level, increase HDL level, change the morphology and number of adipocytes, and increase the expression of leptin receptor in hypothalamus. Conclusion . Acupoint embedding therapy can reduce the level of leptin in blood, increase the number of leptin receptors in hypothalamus, enhance the biological effect of leptin, alleviate the leptin resistance in obese body, change the shape of fat, and regulate the level of blood lipid, so as to achieve the goal of weight loss.